2007
DOI: 10.1095/biolreprod.106.057653
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Associations among Pulses of 13,14-Dihydro-15-keto-PGF2alpha, Luteal Blood Flow, and Luteolysis in Cattle1

Abstract: Luteal blood flow was studied in heifers by transrectal color-Doppler ultrasound. Data were normalized to the decrease in plasma progesterone to <1 ng/ml (Day 0 or Hour 0). Blood flow in the corpus luteum (CL) was estimated by the percentage of CL area with color flow signals. Systemic prostaglandin F2alpha (PGF) treatment (25 mg; n=4) resulted in a transient increase in CL blood flow during the initial portion of the induced decrease in progesterone. Intrauterine treatment (1 or 2 mg) was done to preclude hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 27 publications
12
99
0
8
Order By: Relevance
“…For CL with cavity, the diameter and area of the cavity was subtracted from the total area (Kastelic et al 1990). The percentage of POF wall and luteal tissue with vascular signals was determined subjectively by watching the color Doppler video clip, as previously described (Ginther et al 2007). Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For CL with cavity, the diameter and area of the cavity was subtracted from the total area (Kastelic et al 1990). The percentage of POF wall and luteal tissue with vascular signals was determined subjectively by watching the color Doppler video clip, as previously described (Ginther et al 2007). Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
“…Near ovulation, was shown that an extensive vascularity is formed in the follicular wall until the ovulation occurs (Geva & Jaffe 2000, Reisinger et al 2007). Subjective and objective methods are validated and can be used to measure follicular vascularity in cows and mares (Ginther et al 2007). Previous works showed that follicles with greater diameter resulted in also greater pregnancy rates (Sá Filho et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations of PRL, PGFM, LH, and FSH concentrations were evaluated to detect pulses during Hours 0 to 8, as described [1]. When the coefficient of variation (CV) of the values comprising a fluctuation from beginning to ending nadirs was at least three times greater than the mean intra-assay CV, the fluctuation was considered to be a pulse.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
“…Assay of plasma concentrations of progesterone (P4) and transrectal ultrasonic evaluation of the CL and percentage of CL with color-Doppler blood flow signals can be used to evaluate the CL in large animals [1,2]. In mares, the average day of transition from preluteolysis to luteolysis is Day 14 (Day 0 ϭ ovulation), based on collection of hourly blood samples [3].…”
Section: Introductionmentioning
confidence: 99%